TRAINING IN MAKING CRACKERS FROM LEFTOVER RICE FOR INCREASING FAMILY INCOME IN GAMPONG ULEE JALAN BANDA SAKTI DISTRICT LHOKSEUMAWE CITY - Likdanawati; Hamdiah; Cut Putri Mellita Sari; Rina Rahayu; Mona Adilia (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
Gampong Ulee Jalan is in the Banda Sakti sub-district of Lhokseumawe City. This gampong is located in the Malacca Strait crossing area. Apart from that, the majority of people in Ulee Jalan gampong are Acehnese and there are some mixtures of other tribes. Gampong Ulee Jalan Banda Sakti District, Lhokseumawe City consists of 4 (four) hamlets named Mesjid Hamlet, Bahagia Hamlet, Sejahtera Hamlet, and Dayah Hamlet. The problems faced by the people of Ulee Jalan gampong are the problem of poverty and low education and lack of knowledge about technology for processing leftover rice which is always at home every day and leftover rice from celebrations, low knowledge in running a business and marketing and limited employment opportunities so that employment opportunities are needed. new to increase people's income, especially family income. To solve the problems faced by partners, training and assistance is provided in making leftover rice crackers so that they are worth selling, increasing entrepreneurial skills and creating new business opportunities in making leftover rice crackers, which in the end can increase people's income in general and family income in particular. The aim of community service activities (PKM) is expected to be able to make a contribution, especially to the women of Ulee Jalan village, to further increase their creativity to make optimal use of the potential that exists in the mothers through training in making crackers from leftover rice so that the mothers can create jobs. and increase knowledge and understand how to increase family income. The activity implementation method is carried out by (1) introducing products/crackers resulting from processing leftover rice into crispy and nutritious crackers whose processing does not require modern equipment, (2) training and assistance in making leftover rice crackers which are rich in nutrition. (3) product packaging. The result of this activity is increased knowledge and skills of partners in processing leftover rice.